Heterogeneous Motives in the Trust Game: A Tale of Two Roles - Espín, Antonio M.; Exadaktylos, Filippos; Neyse, Levent (Frontiers in Psychology, 2016)
Abstract Levels of trust and trustworthiness have important externalities for the society. But what exactly do these social concepts reflect? Building upon the argument that in typical real-life social exchanges people act simultaneously as both trustors and trustees, we study the impact of individuals’ social motives (or preferences) on their choices in a dual-role Trust Game (TG). We employ data from a large-scale representative experiment (N = 774), where all subjects played both roles of a binary TG with real monetary incentives. Subjects’ social motives were inferred using their decisions in a Dictator Game and a dual-role Ultimatum Game. Next to self-interest and strategic motives we consider preferences for altruism, spitefulness, egalitarianism and efficiency. We demonstrate that there exists considerable heterogeneity in motives in the TG. Most importantly, among individuals who choose to trust as trustors, social motives can differ dramatically as there is a non-negligible proportion of them who seem to act out of (strategic) self-interest whereas others are driven more by efficiency considerations. Subjects’ elicited trustworthiness, however, can be used to infer such motivations: while the former are not trustworthy as trustees, the latter are. We discuss that research on trust can benefit from adding the second player’s choice in TG designs.